Alkoxides-based sol-gel process - a smart way to obtain luminescent powders and films of yttrium garnets - Potdevin, Audrey; Chadeyron, Geneviève; Boyer, Damien; Briois, Valérie; Santilli, Celso V.; Mahiou, Rachid (My University, 2012)
Undoped and rare-earth (RE=Ce, Tb or Eu) doped yttrium garnets have been synthesized in shape of powders and films by an original alkoxides-based sol-gel route. After a short review devoted to the elaboration of yttrium garnets from alkoxides, this chapter will be dedicated to several results highlighting the advantages of the sol-gel process compared to the conventional solid-state reaction for synthesizing this family of materials. In particular, structural, morphological and optical properties of powders and dip-coated or sprayed films will be presented. The changes entailed by the use of a chemical modifier on the crystallization process of Y3Al5O12:Tb powders will be also detailed. © 2012 Nova Science Publishers, Inc. All rights reserved.